2023
DOI: 10.3390/jpm13081251
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Post-PCI Angiography-Derived Fractional Flow Reserve: A Systematic Review and Meta-Analysis of Cohort Studies

Abstract: The post-percutaneous coronary intervention (post-PCI) fractional flow reserve (FFR) can detect suboptimal PCI or residual ischemia and potentially lead to fewer adverse clinical outcomes. We sought to investigate the predictive value of the angiography-derived FFR for adverse cardiovascular events in patients after PCI. We conducted a comprehensive search of electronic databases, MEDLINE, EMBASE, and the Cochrane Library, for studies published until March 2023 that investigated the prognostic role of angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…Even in the post-PCI setting QFR seems an effective technique and can be used to drive prognostic intervention decision making, with lower post-PCI QFR values accurately predicting adverse clinical outcomes [27]. As discussed by Chen et al, post-PCI QFR assessment showed a solid predictive value over future adverse cardiovascular events and this finding was confirmed by another large meta-analysis, with a 58% risk reduction per each 0.1 increase in the post-PCI QFR value [28,29]. In this context, compared with wire-based physiology, QFR has a theoretical additional advantage, as it may allow to predict beforehand the functional result of the angioplasty.…”
Section: Discussionmentioning
confidence: 83%
“…Even in the post-PCI setting QFR seems an effective technique and can be used to drive prognostic intervention decision making, with lower post-PCI QFR values accurately predicting adverse clinical outcomes [27]. As discussed by Chen et al, post-PCI QFR assessment showed a solid predictive value over future adverse cardiovascular events and this finding was confirmed by another large meta-analysis, with a 58% risk reduction per each 0.1 increase in the post-PCI QFR value [28,29]. In this context, compared with wire-based physiology, QFR has a theoretical additional advantage, as it may allow to predict beforehand the functional result of the angioplasty.…”
Section: Discussionmentioning
confidence: 83%